2016
DOI: 10.1142/s1793545816500176
|View full text |Cite
|
Sign up to set email alerts
|

In vivosubsite classification and diagnosis of oral cancers using Raman spectroscopy

Abstract: Oral cancers su®er from poor disease-free survival rates due to delayed diagnosis. Noninvasive, rapid, objective approaches as adjuncts to visual inspection can help in better management of oral cancers. Raman spectroscopy (RS) has shown potential in identi¯cation of oral premalignant and malignant conditions and also in the detection of early cancer changes like cancer-¯eld-e®ects (CFE) at buccal mucosa subsite. Anatomic di®erences between di®erent oral subsites have also been reported using RS. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
3
25
1
Order By: Relevance
“…35 Paidi et al 36 discovered that the use of RS is feasible to detect changes in the stroma of the lung microenvironment in response to primary breast tumors. Sahu et al 37 found that early malignancyassociated changes in normal contralateral sites of oral cancer may lead to anatomical variability and cause misclassification between contralateral and tumor. Boppart et al 38 raised the question that molecular surgical margin may be a better way to define tumor boundary than the "gold standard" structural tumor margin.…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 99%
“…35 Paidi et al 36 discovered that the use of RS is feasible to detect changes in the stroma of the lung microenvironment in response to primary breast tumors. Sahu et al 37 found that early malignancyassociated changes in normal contralateral sites of oral cancer may lead to anatomical variability and cause misclassification between contralateral and tumor. Boppart et al 38 raised the question that molecular surgical margin may be a better way to define tumor boundary than the "gold standard" structural tumor margin.…”
Section: Journal Of Biomedical Opticsmentioning
confidence: 99%
“…Moreover, Schmälzlin et al offered application of the Raman imaging system to study cancer biopsy samples . Many research teams have been trying to increase the efficiency of diagnostics by using more sensitive and expensive equipment (high spectral resolution, deeply cooled detectors, etc.). Indeed, the RS and AF methods are based on the detection of spectral differences of tumor and normal tissue, and an increase in spectral resolution should seemingly lead to an increase in the efficiency of cancer type recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy (RS), a vibrational spectroscopic method sensitive to subtle biochemical perturbations in biological systems, has been extensively explored in disease and cancer diagnosis , including management of oral cancers . More importantly, RS has also shown potential in identifying subclinical cancer‐field effects (CFEs) or malignancy‐associated‐changes (MACs) in oral cancer patients .…”
Section: Introductionmentioning
confidence: 99%